Effects of industrial noise on circumpulpar dentin - a field emission scanning electron microscopy and energy dispersive spectroscopy analysis - Cavacas, Maria Alzira (2013)
"Chronic exposure to Industrial Noise (IN), rich in Low Frequency Noise (LFN), causes systemic fibrotic transformation and sustained stress. Dental wear, significantly increased with exposure to LFN, affects the teeth particularly through the circumpulpar dentin. Our goal is to understand the consequences of IN exposure on the circumpulpar dentin of Wistar rats. 10 Wistar rats were exposed to IN for 4 months, according to an occupationally simulated time schedule and 10 animals were used as age-matched controls. The first and the second upper and lower molars of each animal were processed for observation by Field Emission Scanning Electron Microscopy (FESEM) and Energy Dispersive Spectroscopy (EDS) analysis was performed. In exposed animals FESEM showed a 2.0 to 6.0 μm-dense mineral band between dentin and the pulp with no regular continuity with the tubules. This structure had a few tubules where the odontoblasts processes could be observed embedded within the band and collagen fibers were trapped inside. EDS analysis revealed that it was hydroxyapatite similar to dentin, with a higher carbon content. FESEM results show that the band may be tertiary reparative dentin formed by odontoblast-like cells, but the increased amount of carbon (EDS) could mean that it is sclerotic dentin. IN should be acknowledge as a strong stimulus, able to cause an injury to odontoblasts and to the formation of reparative tertiary dentin, in a process that may accelerate the aging of the teeth, either by direct impact of acoustic pressure pulsations or by increased stress and dental wear."